Functional discomfort and a shift in midwifery paradigm. Issue 3 (September 2015) - Sanders, Ruth
Abstract Objective To determine and critically examine maternity attitudes surrounding labour pain and how midwives can best facilitate women navigating intrapartum discomfort without relying on 'pain-relief' strategies or immediate recourse for analgesic assistance. Approach This article examines current literature using seminal research and wider international perspectives, exploring the complex and fluctuating needs of women negotiating the composite factors of labour discomfort are investigated. Findings Factors such as birth environment, fear, midwifery presence, and self-efficacy, have a significant impact on the uptake of intrapartum analgesia. A holistic view of intrapartum discomfort is needed to shift the current paradigm of pathologising labour pain into one which situates it as a source of positive physiology and functional discomfort. Conclusion Continuing to practice with a pharmacological outlook, aiming to rid the labouring body of discomfort, is reductionist for both midwives and women. Midwives must seek to employ a new lexicon with which to communicate and facilitate women within the dynamic and continually changing territory of labour. If this conceptual shift is realised, the subsequent positive sequalae of women rediscovering their innate birthing capabilities could create a situation where birth can be considered as an aesthetic peak experience, improving satisfaction on both sides of the midwife-mother diad.